FUNCTIONAL DISORDERS OF THE DIGESTIVE TRACT IN INFANTS - M.Yu. Denisov; E.Yu. Shvedkina (Union of pediatricians of Russia, 2010)
The article provides results of studying the frequency of occurrence of symptoms for functional disorders of the digestive tract in children in their first half a year who are under different types of infant feeding strategies. It was found that 79.6% of children in their first half a year had been diagnosed with the symptoms for disorders of gastrointestinal tract (GIT) function. The most frequent were intestinal colics (56.1%), posseting (53.1%) and delayed defecation (29.6% of cases). A correlation between the intestinal colics, flatulence and posseting was established. It was found that various functional disorders of the digestive tract in infants have common links of pathogenesis. The authors convincingly demonstrated that an infant with functional disorders of GIT needs comprehensive therapy. Key words: intestinal colics, flatulence, posseting, digestive tract, functional disorders, infants, infancy. (Pediatric Pharmacology. - 2010; 7(5):88-92)